2012
DOI: 10.1128/mcb.06318-11
|View full text |Cite
|
Sign up to set email alerts
|

RNA Profiling and Chromatin Immunoprecipitation-Sequencing Reveal that PTF1a Stabilizes Pancreas Progenitor Identity via the Control of MNX1/HLXB9 and a Network of Other Transcription Factors

Abstract: dPancreas development is initiated by the specification and expansion of a small group of endodermal cells. Several transcription factors are crucial for progenitor maintenance and expansion, but their interactions and the downstream targets mediating their activity are poorly understood. Among those factors, PTF1a, a basic helix-loop-helix (bHLH) transcription factor which controls pancreas exocrine cell differentiation, maintenance, and functionality, is also needed for the early specification of pancreas pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
42
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 38 publications
11
42
1
Order By: Relevance
“…Our results indicate that this binding is important during development, because Ptf1a and Rbpjl expression decreases dramatically after Nr5a2 inactivation, and, conversely, Nr5a2 expression is lost upon Ptf1a inactivation. Thompson and colleagues have shown that PTF1A also resides on the Nr5a2 enhancer region that we identified in this study in chromatin from an immortalized acinar cell line that has a gene expression profile consistent with embryonic progenitor cell character (Thompson et al, 2012). Thus, it appears that the regulatory interactions persist throughout pancreatic development.…”
Section: Mpc and Pre-acinar Cell Expansionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our results indicate that this binding is important during development, because Ptf1a and Rbpjl expression decreases dramatically after Nr5a2 inactivation, and, conversely, Nr5a2 expression is lost upon Ptf1a inactivation. Thompson and colleagues have shown that PTF1A also resides on the Nr5a2 enhancer region that we identified in this study in chromatin from an immortalized acinar cell line that has a gene expression profile consistent with embryonic progenitor cell character (Thompson et al, 2012). Thus, it appears that the regulatory interactions persist throughout pancreatic development.…”
Section: Mpc and Pre-acinar Cell Expansionsupporting
confidence: 62%
“…8G, 1.5 turn). This is a particularly rigorous test, because binding by the trimeric PTF1 complex requires paired E-and TC-boxes with unit DNA helical turn spacing (Beres et al, 2006;Thompson et al, 2012). Thus, the activity of the CUR depends on the distal PTF1-binding site, which in turn requires the binding of the complete PTF1 complex, and not on the binding of the bHLH subcomplex or an RBP subunit independently.…”
Section: The Ptf1 Complex Drives Nr5a2 Expression In the Pancreasmentioning
confidence: 99%
“…Both genes represent primary ('first tier') regulators of pro-pancreatic MPC character (Burlison et al, 2008;Kawaguchi et al, 2002;Krapp et al, 1998;Jonsson et al, 1994;Offield et al, 1996;Thompson et al, 2012). We speculate that acquiring a stable Ptf1a + Pdx1 + co-positive state, at a particular stage of organ development, is an efficient feedforward method of specifying and then committing to the pancreatic fate.…”
Section: Endodermal Progenitor Competencementioning
confidence: 80%
“…Various types of mutation, such as insertion, deletion or substitution, were found resulting in nonsense mutation, frame shift mutation, or abnormal splicing [73]. Thompson et al showed that both Ptf1a and Hlxb9 were expressed in the pancreas, and that Ptf1a was required for Hlxb9 expression [112]. Although it is not clear whether PTF1A is involved in human CRS or CS, the evidence from this study implies that misexpression of PTF1A and possibly HLXB9 in the caudal abnormalities may cause CRS.…”
Section: Cyp26a1mentioning
confidence: 99%